A Case of Turner’s Syndrome, with Apparently Normal Sex Chromatin and Chromosome Findings - BUTLER, MERLIN G. (Nebr Med J, 1979)
A case of an infertile female with 46 chromosomes and apparently normal sex chromatin is reported. The clinical findings resemble those of Turner’s syndrome with 45 chromosomes (designated as 45,X) and abnormal sex chromatin findings. A gonadal biopsy revealed streaked ovaries with fibrous connective tissue and no evidence of ovulation or primordial follicles. Chromosome studies of the peripheral blood lymphocytes, skin, and ovarian tissue revealed the presence of 46 chromosomes and an isochromosome of the long arm of the X chromosome, designated as 46,X,i(Xq). There was no evidence of chromosomal mosaicism. This case emphasizes the importance of performing a complete chromosome analysis in patients who present with the clinical features of Turner’s syndrome, but who have apparently normal sex chromatin findings. The analysis can effectively rule out the syndrome, and can also provide a basis for prognosis and management of the patient, including genetic counseling of the family members.